Nonlinear axisymmetric response of thin FGM shallow spherical shells with ceramic-metal-ceramic layers under uniform external pressure and temperature - Anh, Vu Thi Thuy; Duc, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics; Vol 29 No 2, 2013)
Abstract: To increase the thermal resistance of various structural components in high-temperature environments, research reports focusing nonlinear axisymmetric response of thin FGM shallow spherical shells with ceramic – metal – ceramic layers (S-FGM) under uniform external pressure and temperature. Equilibrium and compatibility equations for shallow spherical shells are derived by using the classical shell theory and specialized for axisymmetric deformation with both geometrical nonlinearity and initial geometrical imperfection. One-term deflection mode is assumed and explicit expressions of buckling loads and load–deflection curves are determined due to Galerkin method. Stability analysis for a clamped spherical shell shows the effects of material and geometric parameters, edge restraint and temperature conditions, and imperfection on the behavior of the shells. The results were compared with the P-FGM spherical shell symmetry axis (ceramic – metal). Keywords: axisymmetric response, S-FGM ceramic-metal-ceramic, thin shallow spherical shells, external pressure, thermal loads.